Peran Penggunaan Teknologi Terhadap : Pendidikan - Bangkit Nugraha; Ariska Sara; Izmi Nurul Azizah; Ridha Nisa Maulida; Sabina Sabina; Rafif H Mukmin; Rika Widawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Technology has led to a new world order without renewable technology, the world of education would not be as efficient as it is today. Not only in the world of education, technology also affects the economy, social, culture and geopolitics. Besides the technology itself, it is our obligation to be educated because if we only use technology without insight, it is feared that we are governed by technology, not us. One of the advances in the world of education is artificial intelligence which greatly helps the educational process but must also be inserted with critical thinking not to be dissolved and drifted in the ease of this very sophisticated technology.